2018
DOI: 10.7567/apex.11.081101
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature (150 °C) activation of Ar+O2+H2-sputtered In–Ga–Zn–O for thin-film transistors

Abstract: In–Ga–Zn–O (IGZO) sputtering in an Ar, O2, and H2 atmosphere followed by annealing represents an effective method for defect reduction of the resulting films. The carrier density of Ar+O2+H2-sputtered IGZO films increases with increasing H2 amount during sputtering; however, we found that the increased carrier density was markedly decreased by annealing even at 150 °C. The Ar+O2+H2-sputtered IGZO was used as the active channel in thin-film transistors (TFTs), which led to markedly improved electrical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
(40 reference statements)
3
23
0
Order By: Relevance
“…The radius of the Schottky contact was 100 μm for Schottky diodes, and L of 10 μm and W of 100 μm for MES-FETs. The detailed fabrication process of the devices appears elsewhere [14][15][16][17]. To investigate the electronic states in IGZO:H films, hard X-ray photoelectron spectroscopy (HAXPES) analysis with an excitation X-ray energy of 7940 eV was performed.…”
Section: Device Fabrication Processesmentioning
confidence: 99%
“…The radius of the Schottky contact was 100 μm for Schottky diodes, and L of 10 μm and W of 100 μm for MES-FETs. The detailed fabrication process of the devices appears elsewhere [14][15][16][17]. To investigate the electronic states in IGZO:H films, hard X-ray photoelectron spectroscopy (HAXPES) analysis with an excitation X-ray energy of 7940 eV was performed.…”
Section: Device Fabrication Processesmentioning
confidence: 99%
“…Furthermore, Aman and Magari et al reported that hydrogen in hydrogenated IGZO acts as a carrier suppressor through annealing by forming metal-hydrogen (M-H) bonds when hydrogen was intentionally added during IGZO deposition. 12,13) In this presentation, we propose a hydrogenated polycrystalline IGO (poly-IGO:H) for use in a channel material of the TFTs. An intentionally doped hydrogen in IGO:H film suppressed the crystallization during the film deposition.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] a-IGZO TFTs have recently been manufactured using various methods, including physical vapor deposition (PVD), [9][10][11][12] chemical vapor deposition, [13][14][15][16] spin-on-glass, and electroplating. [17][18][19][20] Among these, the sputtering deposition used in PVD has a high commercial potential for mass production because of the benefits of a high deposition rate, a low substrate temperature, and relatively easy thin-film composition control. [21][22][23] As the size and resolution of activematrix displays increase, oxide-based TFTs with faster reaction speeds are required.…”
Section: Introductionmentioning
confidence: 99%